Neuropsychiatric Manifestations of Lyme Disease: A Literature Review of Psychiatric and Cognitive Impacts - Šegždaitė, Gabija; Aliukonytė, Odeta; Pociūtė, Kamilė (Acta medica Lituanica, 2025)
Background: Lyme disease can lead to neuropsychiatric symptoms like depression, anxiety, and cognitive issues, often mimicking primary psychiatric disorders. This paper examines the connection between Lyme disease and neuropsychiatric outcomes to improve diagnosis and treatment.Materials and Methods: The PubMed database was searched for scientific literature sources. Publications published in English in 2019–2024 were selected. All psychiatric symptoms and disorders found to be associated with Lyme disease were included. For neurological symptoms, the analysis focused on studies addressing cognitive dysfunction.Results: Acute neuroborreliosis may have minimal effects on the cognitive function and typically resolves well with treatment. However, some studies suggest that Lyme disease can affect the patients’ cognitive abilities, leading to impairments in verbal fluency, attention, and memory, with a few isolated dementia-like cases highlighting the need for careful diagnosis. Nevertheless, recent large-scale studies show no increased risk of dementia. Regarding psychiatric symptoms, findings are also inconsistent, with some studies suggesting an increased risk of depression, anxiety, sleep disturbances, and other mental health conditions, while others find no such association.Conclusions: There is no strong evidence supporting Lyme disease’s role in long-term cognitive or psychiatric disorders. However, an early diagnosis and timely antibiotic treatment remain crucial in minimizing long-term consequences and improving patient outcomes.